Effect of breastfeeding for 6 months on disease outcomes in patients with Kawasaki disease. - Mindy Ming-Huey Guo; I-Hsin Tsai; Ho-Chang Kuo (PLoS ONE)
Background Kawasaki disease (KD) is a systematic vasculitis that occurs predominantly in young children, and is the leading cause of acquired heart disease in children younger than five-years-old in developed countries. Although the etiology of KD is unknown, it is believed to be an inflammatory disease resulting from abnormal immune responses to possible environmental or infectious stimuli in genetically predisposed individuals. Breast milk contains numerous anti-inflammatory factors which may protect against allergic and autoimmune diseases. In this study we tried to examine the effect of breastfeeding for 6 months or more on disease outcomes in patients with Kawasaki disease. Methods A retrospective cohort study of 249 KD patients admitted from 1999- 2013 who were older than 6 months at time of diagnosis and had data regarding breastfeeding in the first 6 months of life. Demographic, clinical and laboratory data was collected by chart review. Continuous data was compared using Student's t-test and categorical variables were compared using Chi-square. Stepwise multivariate regression of all demographic factors was performed. Results Breastfeeding for 6 months or more was associated with a shorter total duration of fever (5.980± 1.405 Vs. 6.910 ± 2.573 days, p = 0.001) and a lower risk of developing persistent coronary artery lesions (CALs) (7.8% Vs. 20.2%, p-value = 0.039) on univariate analysis. Multivariate regression of all factors associated with CALs including breastfeeding for 6 months found that only the presence of CALs at baseline (β-coefficient = 0.065, p < 0.001) and white blood count (β-coefficient = 0.065, p = 0.018) remained significant after regression analysis. Conclusions Breastfeeding for 6 months or more was associated with a shorter duration of fever and a lower risk of persistent CAL formation in patients with KD on univariate analysis, although this effect may be modest when other factors such as the presence of CALs at baseline and white blood cell count are also taken into consideration.